Changes of Osteopontin in the Aqueous Humor of the DBA2/J Glaucoma Model Correlated with Optic Nerve and RGC Degenerations - Birke, Marco; Neumann, Carolin; Birke, Kerstin; Kremers, Jan; Scholz, Michael (Investigative Ophthalmology & Visual Science, 2010)
PURPOSE. To identify age-dependent regulated aqueous humor (AH) factors in DBA2/J (D2J) mice and to correlate them with optic nerve degeneration and intraocular pressure (IOP) by population and individual analysis.METHODS. AH samples of D2J mice aged 2 (n = 3), 7 (n = 5), and 10 months (n = 14) were analyzed by mouse cytokine antibody array. Ten-month samples were classified into eyes with (D2J+) or without (D2J-) optic neuropathy. Ten-month-old C57/B16 (B6; n = 13) and DBA2/Rj (D2Rj; n = 15) mice served as controls. IOP was recorded from 2 to 10 months. Individual AH osteopontin (OPN) was determined in 31 D2J eyes (10 months) and was correlated with optic neuropathy and IOP. OPN mRNA was detected by in situ hybridization. OPN blood plasma content of D2J and B6 was monitored from 8 to 10 months. Effect of OPN on cell survival in the ganglion cell layer (GCL) or metabolism was tested in ex vivo-cultured D2Rj eyes and murine neuronal precursors.RESULTS. In array analysis, OPN was detected in 10-month-old D2J mice only. They significantly differed between D2J- and D2J+ (P = 0.006). By Western blot analysis, a sevenfold OPN increase in D2J+ was determined compared with B6. Individual analysis confirmed the positive correlation of OPN with optic neuropathy. IOP was not correlated with OPN. OPN blood plasma contents steadily increased with age in D2J. OPN+ cells were detected within the ciliary body of D2J, and OPN+ RGCs were approximate to 30% reduced. OPN treatment inhibited cell degeneration within the GCL in ex vivo-cultured D2Rj eyes and increased the metabolic activity of neuronal precursor cells.CONCLUSIONS. OPN is an age-dependent increased AH factor associated with degeneration of the optic nerve in D2J mice. By modulating the metabolism of neuronal cells, deregulated levels of OPN could be involved in degenerative processes affecting RGCs or optic nerve axons in the D2J model. (Invest Ophthalmol Vis Sci. 2010; 51:5759-5767) DOI:10.1167/iovs.105558

Cytokine-dependent ELAM-1 induction and concomitant intraocular pressure regulation in porcine anterior eye perfusion culture - Birke, Marco; Birke, Kerstin; Lütjen-Drecoll, Elke; Schlötzer-Schrehardt, Ursula; Hammer, Christian (Investigative Ophthalmology & Visual Science, 2011)
To demonstrate the capacity of interleukin (IL)-1 to simultaneously lower intraocular pressure (IOP) and induce trabecular ELAM-1 expression in one experiment and to test for IL-6 accordingly and evaluate the role of transforming growth factor (TGF)-?2 as an IL-1 antagonist.Forty-two porcine eyes were subjected to trabecular meshwork (TM) perfusion with IL-1?, -1?, or -6 for 48 hours. Twelve of the IL-1?-treated eyes also received TGF-?2 for the final 24-hour period. Polymerase chain reaction and Western blot analyses of ELAM-1 expression were then performed on harvested TM samples. mRNA regulation of IL-1?, IL-1?, IL-6, TGF-?2, and P-selectin (SELP) was determined.IL-1? and -1? treatment augmented outflow facility approximately threefold while inducing ELAM-1. IL-6 perfusion neither changed IOP nor induced ELAM-1. IL-1?/TGF-?2 double treatment significantly counteracted the IL-1-induced IOP decrease and markedly reduced the degree of ELAM-1 mRNA upregulation from 22.3- to 3.1-fold, and ELAM-1 protein from 1.9- to 1.2-fold. IL-1? mRNA was upregulated 5.3-, 3.3-, and 5.5-fold after perfusion with IL-1?, -1?, and -1?/TGF-?2, respectively. The respective values for IL-6 mRNA were 2.0-, 2.1- and 2.4-fold. Expression of IL-1? and TGF-?2 mRNA remained unchanged. IL-6 perfusion had no discernible regulatory effect.Simultaneous demonstration of IL-1's lowering of IOP and inducing trabecular ELAM-1 was achieved for the first time in one experiment, and its possible implications in the pathogenesis of glaucoma was further emphasized. The involvement of an autocrine feedback loop was confirmed in the porcine system. TGF-?2 constitutes a potent IL-1 antagonist for IOP and ELAM-1 regulation.
EVALuna2:21022

Preventive effects of omega-3 and omega-6 Fatty acids on peroxide mediated oxidative stress responses in primary human trabecular meshwork cells - Tourtas, Theofilos; Birke, Marco; Kruse, Friedrich; Welge-Lüssen, Ulrich-Christoph; Birke, Kerstin (PLoS ONE, 2012)
Pathologic processes in glaucoma include increased apoptosis, accumulation of extracellular material in the trabecular meshwork and optic nerve, condensations of the cytoskeleton and precocious cellular senescence. Oxidative stress was shown to generate these alterations in primary ocular cells. Fatty acids omega-3 and -6 are alleged to constitute a prophylaxis against these deleterious effects. Here, we tested actual preventive effects omega-3 and -6 against peroxide induced stress responses in primary human trabecular meshwork cells. Changes of mitochondrial activity, proliferation, heat shock proteins, extracellular matrix components, and inflammatory markers were evaluated. Alterations of the cytoskeleton were evaluated by phalloidin labeling. Here we report a repressive effect of omega-6 on metabolic activity and proliferation, which was not detected for omega-3. Both agents were able to prevent the anti-proliferative effect of H?O?, but only omega-3 prevented metabolic repression. Expression of heat shock protein 27 was unaltered by both fatty acids, whereas heat shock protein 90 was significantly induced by both. Omega-6 increased fibronectin and connective tissue growth factor synthesis, as well as the amount of secreted fibronectin. Omega-3, instead, induced plasminogen activator inhibitor 1 synthesis. H?O? further increased fibronectin production in omega-6 supplemented cells, which was not the case in omega-3 treated cells. H?O? stimulation of plasminogen activator inhibitor 1 and connective tissue growth factor was repressed by both fatty acids. Both fatty acids appeared to abolish H?O? mediated stimulation of nuclear factor ?B and IL-6, but not IL-1? and IL-8. H?O? induced formation of cross-linked actin networks and stress fibers, which was reduced by preemptive application of omega-3. Omega-6, in contrast, had no protective effect on that, and even seemed to promote condensation. Based on the observed side effects of omega-6, omega-3 appears to be the more beneficial fatty acid in respect of prophylactic intake for prevention of a glaucomatous disease.
EVALuna2:21079